Lexical evolution in the age of artificial intelligence: A comparative literature study of English and Indonesian - Mukti, Muhammad Abdee Praja; Fauzi, Erfan Muhammad (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2025)
This qualitative comparative literature study investigates the lexical evolution driven by artificial intelligence (AI) technologies within English and Indonesian linguistic contexts. Focusing on AI-related vocabulary, such as machine learning, prompts, and fine-tuning, the research critically analyses how these terms emerge, adapt, and shift semantically across both languages. English, identified as a global language, serves predominantly as a lexical innovator and supplier of new technological terms. In contrast, Indonesian demonstrates dynamic lexical negotiation through processes of borrowing, semantic adjustment, and selective localisation. The analysis highlights that these linguistic responses reflect deeper cultural, ideological, and social considerations, wherein borrowed terms often undergo subtle semantic shifts influenced by local perceptions of technology and digital interactions. The study explores hybrid linguistic practices that have arisen, particularly in digital communication, reflecting users’ strategic linguistic choices rooted in cultural identity, technological authority, and social contexts. This hybridity highlights the complexities of language use in the digital age, reflecting the negotiations between global integration and cultural authenticity. This research sheds light on broader implications regarding globalisation, linguistic sustainability, and sociocultural identity, suggesting that future research should further investigate empirical data to enhance our understanding of how communities actively navigate linguistic changes amid technological advancements.